Effectiveness of non-invasive transcranial magnetic stimulation therapy as a therapy for post-stroke visuospatial impairment: A meta-analysis - Albertus Theo Lapian; Finny Warouw; Ansye Grace Nancy Momole; Junita Maja Pertiwi; Gilbert Tangkudung (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Visuospatial disorders refer to deficits in attention, exploration, and interaction with the contralateral side of space that cannot be attributed to primary sensory or motor dysfunction. These disorders are usually caused by lesions in the right hemisphere due to cerebral circulation disorders, such as stroke. Transcranial Magnetic Stimulation (TMS) has emerged as a noninvasive treatment option for addressing visuospatial deficits. Purpose: To evaluate the effectiveness of TMS as a therapy for visuospatial disorders in post-stroke patients. Method: This study was conducted using randomized controlled trials (RCTs) comparing TMS with sham treatment for post-stroke visuospatial impairment identified through searches in Google Scholar, PubMed/Medline, Clinical Key, Wiley Online, Science Direct, ResearchGate, and Neurona. A meta-analysis was conducted to assess the efficacy of TMS therapy for improving visuospatial deficits in post-stroke patients. Results: A total of 189 studies on TMS were identified with four homogeneous articles finally included in the meta-analysis. The analysis combined visuospatial assessments using the Motor-Free Visual Perception Test (MVPT), ​​Star Cancellation Test (SCT), Albert Test (AT), and Line Bisection Test (LBT). The meta-analysis revealed significant findings for the MVPT, with a weighted mean difference (WMD) of 2.43 (95% CI: 1.86 to 3.01, p < 0.001). For LBT, WMD was 2.69 (95% CI: 2.04 to 3.34, p = 0.020). Conclusion: The improvements in visuospatial function observed in participants undergoing TMS suggest that TMS may serve as a potential therapeutic option for post-stroke patients with visuospatial impairment.